The Role of Entrepreneurial Knowledge in Workaholism: an Applied Study of the Opinions of a Sample of Workers in the Diwaniyah Education Directorate - Rahman, Sahar Jabbar (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
The current research aims to uncover the role of Entrepreneurship knowledge in influencing (Innovation, Problem Solving, Skill, and Leadership) in Workaholism, manifested as (Immersion in Work, Motivation at Work, and Enjoyment of Work) among a sample of employees in the Diwaniyah Education Directorate. To achieve this goal, which emerged from the problem statement formulated as the question (Is there a role for Entrepreneurship knowledge in Workaholism among employees in the Diwaniyah Education Directorate?), a descriptive analytical approach was adopted by adopting a questionnaire to collect the necessary data for identifying the levels of research variables. Accordingly, (200) questionnaires were distributed, of which (173) were retrieved, with (12) damaged questionnaires, (27) unretrieved questionnaires, and (161) valid questionnaires for analysis, representing a response rate of (80.5%). To analyze the data obtained, two packages were used: (SPSS & AMOS.V.29) to analyze the results and build the analytical aspect of the research. Based on this, the research yielded several results, the most important of which is the presence of a meaningful correlation between Entrepreneurship knowledge and Workaholism. This is because Entrepreneurship knowledge serves as a powerful tool for enhancing Innovation in the workplace. By fostering an atmosphere where employees embrace new ideas and innovative ways of doing things, Diwaniyah Education Directorate can foster a culture of innovation that pushes performance to greater heights. In line with this research, the Diwan Education Department should strive to design specific training programs to increase the level of Entrepreneurship among staff members, including workshops and courses on Innovation and creativity skills, which will enhance employee efficiency and bolster initiative.